Islamisme Utopian di Indonesia Pasca Orde Baru: Hizbut Tahrir Indonesia (HTI) dan Majelis Mujahidin Indonesia (MMI) - Angela, Deni; Achmad, R. Andriadi (Jurnal Demokrasi dan Politik Lokal, 2024)
This research analyses the development of the Post-New Orde utopian Islamist movement. In addition, this is interesting because the door to reform opened the activities of various groups, including Islam, and to considered a utopia idea in Indonesia. Hizbut Tahrir Indonesia and Majelis Mujahid Indonesia describe representatitves of this group experienced a decline in activities after experiencing familiar terrorism. Meanwhile, the author’s research method carried use to a literature study using data from books, journals, and magazines as a guide during the research. In this research, the author discusses the history of HTI and MMI, especially regarding the beginnings and content of the thoughts of these two organizations as well as history. Apart from that, the author also adds that the content of HTI rejects democracy for various reasons, such as different in goals, function, and perceived secular teachings which are packaged in the form of a comparison table with democratic elections. In addition, the author gives an analysis and explanation of the activities of the two Islamic organizations in the form of da’wah methods, mobilization movements, and the ambitious utopia, that provides existence in Indonesia.